Preparation of micro/mesoporous colloidal photonic crystals and their applications for vapor sensing - LIM, YUN (2016)
Photonic crystals (PCs) are a special class of photonic stop band material, whose dielectric constants are dependent on the structural periodicity. Photons with energy in the photonic band gaps cannot pass through PCs. Thereby, PC devices are designed by people to manipulate light. Colloidal photonic crystals (CPCs) are PC materials that self-assemble by one or several kinds of monodisperse colloidal nanoparticles. Due to their simple, fast and efficient preparation processes, CPCs have propelled much research since its discovery. Mesoporous Silica nanoparticles (MSNs) are a group of mesoporous materials with well-ordered mesopore structures and pore sizes usually ranging between 2-50 nm. Meanwhile, Zeolitic-Imidazolate frameworks (ZIFs) are typical microporous materials which have been dominating the stage as the most prominent porous materials ascertained till date. Both MSNs and ZIFs have distinguished themselves to be potential building blocks for the preparation of PCs. The large surface areas, ordered and controllable pore structures, narrow distribution of pore sizes and modifiable surfaces of MSNs and ZIFs have rendered them great potential in gas adsorption and separation, catalysis, battery, sensors and drug delivery applications. Herein, the present study reports the preparation of microporous or mesoporous CPCs by self-assembly of uniform ZIFs or MSNs nanoparticles; and investigation of their properties for vapor sensing. We believe that the combination of large surface areas and strong adsorption abilities of microporous or mesoporous materials, coupled with the light manipulation capabilities of PCs, will give rise to synergistic effects that will be useful for applications in visible read-out for gaseous adsorption and separation, vapor sensing and dynamic anti-counterfeiting.